The Design and Practice of the General Art Course of Jung’s “Active Imagination” Infused with “Mask” Creation - Wu, Feng-chu (IJRDO- Journal of Educational Research, 2018)
This study takes the "Mask" as the main pillar and infuses it in Jung’s "Active Imagination". Hence, the general art course design is developed, which utilizes art as a way of self-examination and transforms the negative emotions into positive thoughts. The subjects of this study are 46 students who are enrolled in a university’s general art course, on whom this study carries out three-stage courses featuring "My Magical Mask". This study carries out qualitative analysis on students’ process of creation with "the Learning Effect Self-assessment Scale" and "the Teaching Effect Questionnaire". This study shows that students’ symbolic masks are closely connected to psychology, life experience, and cultural environment; also similarities and differences are found in both genders. The course shows positive impact on student’s self-awareness, relieving stress, listening and respect, creative thinking, aesthetic appreciation and so on, and can effectively guide students to learn positive self-therapy. Therefore, this study can provide new thoughts in terms of university’s general art education.